Molecular evolution of the genomic RNA of apple stem grooving Capillovirus - Liebenberg, Annerie; Hell, Rüdiger (Journal of molecular evolution, 2012)
The complete genome of the German isolate AC of Apple stem grooving virus (ASGV) was sequenced. It encodes two overlapping open reading frames (ORFs), similarly to previously described ASGV isolates. Two regions of high variability were detected between the ASGV isolates, variable region 1 (V1, from amino acids (aa) 532 to 570), and variable region 2 (V2, from aa 1,583 to 1,868). The phylogenetic analysis of the V1 and V2 regions suggested that the ASGV diversity was structured by host plant species rather than geographical origin. The dN/dS ratio between nonsynonymous and synonymous nucleotide substitution rates varied greatly along the ASGV genome. Most of ORF1 showed predominant negative selection except for the two regions V1 and V2. V1 showed an elevated dN and an average dS when compared to the ORF1 background but no significant positive selection was detected. The V2 region of ORF1 showed an elevated dN and a low dS when compared to the ORF1 background with an average dN/dS ≈ 3.0 indicative of positive selection. However, the V2 area includes overlapping ORFs, making the dN/dS estimate biased. Joint estimates of the selection intensity in the different ORFs by a recent method indicated that this region of ORF1 was in fact evolving close to neutrality. This was convergent with previous results showing that introduction of stop codons in this region of ORF1 did not impair plant infection. These data suggest that the elimination of a stop codon caused the overprinting of a novel coding region over the ancestral ORF.
Gesehen am 10.11.2018